تأثير موعد العدوى بفيروس موزاييك الخيار في نمو نباتات الفليفلة وإنتاجها في الزراعةالحقلية في محافظة اللاذقية. - إسماعيل, عماد داؤد; سمرة, بديع محمد; العجورية, حلا عدنان (Latakia University Journal -Biological Sciences Series, 2016)
أجريت الدراسة في قرية المتركية الواقعة في السهل الساحلي الجنوبي لمدينة اللاذقية خلال العام 2014، بهدف دراسة تأثير فيروس موزاييك الخيارCucumber mosaic virus(CMV,الجنسCucumovirus,العائلة Bromoviridae)في نمو الهجين ESTAR F1 Hوتطوره، والذي يتبع مجموعة الفليفلة غير الحريفة مع الصنف Demer. شملت الدراسة 8 معاملات (أربع معاملات لكل صنف)؛ إذْ تمت العدوى الميكانيكية بالفيروس في ثلاثة مواعيد مختلفة (قبل الإزهار, وفي أثناء الإزهار, وبعد الإزهار)، إضافة إلى الشاهد غير المعدىبالفيروس.تبين نتيجة الدراسة ظهور أعراض الإصابة بفيروس موزاييك الخيار على نباتات الهجين غير الحريف قبل الصنف الحريف ب4 أيام,وكانت الأعراض على شكل تجعد الأوراق وتشوهها،و ظهور بقع صفراء عليها،وتقزم النبات.أثرت العدوىبالفيروس في عدد الأوراق,وعدد الفروع، وكمية الإنتاج، وكانت أعلى نسبة تأثير في النباتات المعداة بالفيروس قبل تفتح الأزهار في الصنفين كليهما ؛ إذْ بلغ متوسط عدد الأوراق في النبات الواحدالهجين ESTAR F1 H130ورقة/النبات في العدوى قبل تفتح الأزهاربالمقارنةمع الشاهد170ورقة/النبات, ومتوسط عدد الفروع 43,4 فرعاً/نباتاً مقارنة مع 56,7 فرعاً/نباتاًفي الشاهد الهجين ESTAR F1 H. وانخفضت كمية إنتاج النبات الواحد في العدوى قبل تفتح الأزهار إلى 700,8 غ/النبات مقارنة مع 1267,5 غ/النبات في الشاهد الهجين ESTAR F1 H، وأخذت نتائج الصنفDemer المنحى نفسه، ولكن تأثير الإصابة فيه كان أقل من الهجين ESTAR F1 H.انخفض تأثير العدوى بالفيروس في أثناء الإزهار،و كانت أقل من النباتات المعداة قبل الإزهار، وأكثر من النباتات المعداة بعد الإزهار، وكانت الفروق معنوية بين الشاهد والنباتات المعداة قبل الإزهار في الصنفين كليهما. This study was conducted in the village of Almetrkyah located in the southern coastal plain of Lattakia city during 2014. In order to study the effect of Cucumber mosaic virus on growth and development of two varieties of peppers, hybrid ESTAR F1 H (sweet pepper) and Demer(spicy pepper). This study included eight treatments, four treatments for each variety. Plants were mechanically inoculated in three different stages, pre- flowering bloom, flowering andpost-flowering stages each beside its non-inoculated control. The result should that, the appearance of Cucumber mosaic virus symptoms on infected sweet hybrid, was within four days before its appearance on inoculated spicy variety,symptoms were leaf crinkle, leaf deformation, yellow patches and plant stunting. Inoculated plants showed reduction in number of leaves, number of branches and yield. Plants in pre flowering bloom stage were more effected by virus infection in both varieties. Meannumber of leaves per plant of ESTAR F1 H hybrid were 130 in pre flowering bloom stage compared with 170 leaf/plant in the control treatment. Mean number of branches per plant of ESTAR F1 H hybrid were 43,4 branch/plant in pre flowering bloom stage compared with 56,7branch/plant in the control treatment. Total pepper production per plant was 700,8g in infected plants in preflowering bloom stage compared with 1267,5g/plant in ESTAR F1 H hybrid control. Results of Demer variety take the same results of ESTAR F1 H hybrid. The effect of virus infection on pepper plants were reduced when inoculation were done during flowering stage and post-flowering stage, differences were significant between inoculated plants in both varieties.